Prediction Of Cigarette And Tobacco Price Index In Tangerang City Using Ses And Double Linear Exponential Smoothing - Saudi, Jeremy Heriyandi (Communication In Research And Publications, 2025)
The cigarette and tobacco price index is a crucial indicator that reflects changes in prices and demand in the tobacco market. Accurate predictions of this index are essential for the government and industry players in planning policies and business strategies. This study aims to forecast the cigarette and tobacco price index in Banten Province using the Single Exponential Smoothing (SES) and Double Linear Exponential Smoothing (DES) methods. The data used in this research comprises monthly cigarette and tobacco price index data from January 2021 to December 2023. SES and DES models are applied for prediction, and their results are evaluated using performance indicators such as Mean Absolute Percentage Error (MAPE). The research findings indicate that both methods are highly effective in predicting the cigarette and tobacco price index, with the SES method providing slightly more accurate predictions than the DES method. The MAPE error value for the SES method is 0.51%, while the DES method has a MAPE error value of 0.65%. These results are expected to contribute to policymakers and industry players in understanding price trends and making more informative decisions.